2007
DOI: 10.1159/000099033
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Newly Diagnosed Bladder Cancer, Bladder Cancer Recurrence and Bladder Cancer in Patients with Hematuria Using Quantitative RT-PCR of Urinary Survivin

Abstract: Background/Aims: Survivin mRNA in urine was measured to detect newly diagnosed bladder cancer, bladder cancer recurrence and bladder cancer in patients with hematuria. Methods: We have investigated urinary survivin mRNA of 118 voided urine specimens, including 24 patients with bladder cancer, 50 with bladder cancer history, 68 not known to harbor bladder cancer, and 55 with hematuria using quantitative reverse transcriptase polymerase chain reaction. β-Actin mRNA expression was also examined and used as an end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 27 publications
1
23
0
2
Order By: Relevance
“…Several studies on survivin expression in urinary samples confirmed the potential value of this protein as sensitive marker for early, noninvasive detection of bladder carcinoma (24)(25)(26)(27)(28). In addition, some groups reported a significant association of survivin expression with higher tumor grade and stage, in urinary samples or tissue specimens (24,(29)(30)(31).…”
Section: Deregulated Expression Of Apoptosis Inhibitors Have Beenmentioning
confidence: 90%
“…Several studies on survivin expression in urinary samples confirmed the potential value of this protein as sensitive marker for early, noninvasive detection of bladder carcinoma (24)(25)(26)(27)(28). In addition, some groups reported a significant association of survivin expression with higher tumor grade and stage, in urinary samples or tissue specimens (24,(29)(30)(31).…”
Section: Deregulated Expression Of Apoptosis Inhibitors Have Beenmentioning
confidence: 90%
“…In the same study, survivin expression correlated with disease recurrence and disease-specific mortality, suggesting that survivin expression may represent a diagnosis marker of occult malignancy. Indeed, the detection of urinary survivin by immunochemistry or reverse transcription-PCR seems to be a promising assay to detect both newly diagnosed and recurrent bladder cancer (62,63). Finally, survivin overexpression may be a predictive factor to determine response to chemotherapy and radiotherapy in patients with bladder cancer (64), breast cancer (65), multiple myeloma (66), and lymphoma (67 -69).…”
Section: Role Of Survivin In Cancermentioning
confidence: 99%
“…Survivin expression can be detected in all bladder cancer tissues, but not in normal urothelium specimens (292,293 ). The expression patterns of survivin in patients with bladder cancer can be examined in urine, as can the diagnostic potential of RT-PCR detection of survivin mRNA (294,295 ). Smith et al have developed a polyclonal semiquantitative immunoassay to assess the role of survivin as a urine marker for bladder cancer (291 ).…”
Section: Blca-4mentioning
confidence: 99%